1995
DOI: 10.1016/0092-8674(95)90081-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the yeast MCM3-related protein as a component of xenopus DNA replication licensing factor

Abstract: Replication licensing factor is thought to be involved in the strict control of the initiation of DNA replication in eukaryotes. We identified a 100 kDa protein as a candidate for the licensing factor in Xenopus egg extracts. This protein was required for replication; it bound to sperm DNA before the formation of nuclei and apparently dissociated from the nuclear DNA during the progression of replication without being transported into the nuclei. An immunologically homologous protein in HeLa cells behaved simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
286
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(310 citation statements)
references
References 27 publications
21
286
1
2
Order By: Relevance
“…N-terminal-polyhistidine-tagged Xenopus MCM2 was purified as described elsewhere (51). Affinity purification of Xenopus MCM2-7 proteins from the egg extracts was carried out using anti-MCM2 antibodies, essentially as described previously (52,53). In brief, anti-MCM2 antibodies coupled to Protein A-Sepharose beads were incubated with the egg extracts (LSS) for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…N-terminal-polyhistidine-tagged Xenopus MCM2 was purified as described elsewhere (51). Affinity purification of Xenopus MCM2-7 proteins from the egg extracts was carried out using anti-MCM2 antibodies, essentially as described previously (52,53). In brief, anti-MCM2 antibodies coupled to Protein A-Sepharose beads were incubated with the egg extracts (LSS) for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that glutathione S-transferase (GST)-fused recombinant Xenopus MCM3 (maternal form) fails to be transported into nuclei formed in Xenopus egg extracts. 21 To compare the NLS activity of maternal and zygotic forms of MCM3, we examined the nuclear transport of GST-enhanced green fluorescent protein (EGFP) fused recombinant proteins into nuclei formed in the extracts (Fig. 2B).…”
Section: Characterization Of the Nls-like Motifs Found In Maternal Anmentioning
confidence: 99%
“…MCM homologues have been identified in all eukaryotes, and all are essential for DNA replication (1,(3)(4)(5)(6)(7). The recruitment of these proteins onto replication origins during the G 1 phase of the cell cycle is essential for the formation of a prereplicative complex and initiation of DNA synthesis (8 -12).…”
mentioning
confidence: 99%